Tracing the Roots of Modern Human Rights in Ancient Greek Thought - Ramachandran, Mallika (Morgan Journal of Interdisciplinary Research Studies, 2024)
The establishment of the modern human rights regime, a pivotal development that transpired in the aftermath of the Second World War, marks a watershed moment in the annals of global governance. However, it is imperative to recognize that the foundational bedrock upon which this regime stands embodied by concepts such as freedom, equality, the right to vote, and the notion of natural rights extends its roots far beyond the mid-20th century. These bedrock principles have an intricate lineage, manifesting in various forms throughout history and across diverse cultures. To unravel this historical continuum, one need not look solely to the post-World War II era; rather, a profound exploration reveals that analogous ideals have left indelible imprints across different countries and epochs. Among these cultural tapestries, ancient Greece emerges as a particularly rich and influential backdrop, offering a plethora of ideas that resonate with the very essence of contemporary human rights. In an earnest pursuit of understanding the intricate interplay between ancient wisdom and modern conceptions, the present paper embarks on an insightful examination. Through a meticulous study, it endeavors to illuminate the myriad ideas and features that emanated from ancient Greece, serving as pre-cursors to, and reflections of, the multifaceted concept of human rights as it is comprehended and cherished in our present-day global discourse.